Uso de depredadores, parasitoides y entomopatógenos para el control biológico de plagas y enfermedades de hortalizas con énfasis en tomate ( Solanum lycopersicum l.) - Corrales Paredes, Cristian Javier (2021)
Pests and diseases are included among the main biotic factors that affect tomato yield, with losses estimated between 15% and 95%. This fact imposes the need to make significant efforts to establish efficient control measures. A bibliographic review of the most common pests and diseases in tomatoes was carried out in this study, as well as the most frequently used biocontrol agents. The Scopus and Scielo databases on the biological control of pests and diseases associated with tomato were used as a source of consultation to compile the most frequently used species of parasitoids, predators and entomopathogens. The bibliographic analysis found that a total of 20 species of insects, four of mites, and six of phytopathogens with the highest incidence in the crop have been described. Additionally, it was observed that biological control is mainly used to control insects (50%), followed by phytopathogenic fungi (44%), and to a lesser degree for the control of phytoparasitic nematodes. The organisms used as biocontrol agents showed that insects represent the group most used in biological control programs, either as predators or parasitoids, followed by entomopathogenic fungi and bacteria. Consequently, information on the main biocontrol agents used worldwide is presented. According to the review, many biocontrol agents can be used in both field and greenhouse conditions.